Convergence and regularization results for optimal control problems with sparsity functional - Wachsmuth, Gerd; Wachsmuth, Daniel (ESAIM. Control, optimisation and calculus of variations, 2011)
Optimization problems with convex but non-smooth cost functional subject to an elliptic partial differential equation are considered. The non-smoothness arises from a L1-norm in the objective functional. The problem is regularized to permit the use of the semi-smooth Newton method. Error estimates with respect to the regularization parameter are provided. Moreover, finite element approximations are studied. A-priori as well as a-posteriori error estimates are developed and confirmed by numerical experiments.